International Agricultural Concepts through the Eyes of School-Based Agriculture Education Students - Nathan W. Conner; Sarah Greer; Christopher T. Stripling (Journal of International Agricultural and Extension Education, 2017)
As demands to participate in a global economy increase, American students, who have limited knowledge of international agriculture concepts, must be better educated in terms of international awareness and understanding. The purpose of this study was to identify the attitudes, beliefs, understanding, and desired instructional methods of Tennessee school-based agricultural education students in regards to international agriculture. A descriptive questionnaire comprised of 46 items, which measured four constructs, was used to collect data. The summated means of all students for attitudes, beliefs, understanding, and instruction were 3.81 (SD = .46), 3.81 (SD = .57), 3.76 (SD = .51), and 3.76 (SD = .47), respectively. Findings indicated students hold positive attitudes and beliefs toward international agricultural concepts. In an effort to remain a global leader in science and innovation and to meet the needs of the agricultural employers, State Departments of Education should consider providing resources for the development, testing, and implementation of internationalized curricula. If not currently internationalized, other countries should also consider internationalizing their curricula and determine how best to equip students with the skills and knowledge necessary to work in a globalized economy.
Keywords: Globalization; International Agriculture; School-Based Agriculture Education